Pengembangan Media Pembelajaran Flipbook Digital Materi Sistem Pencernaan Manusia untuk Peserta Didik Tunadaksa - Aisyah, Feren Salsabila; Firdaus, Talitha Syahda; Muchtar, Tekad Tegar Ksatria; Widajati, Wiwik (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Learners with physical disabilities often face significant challenges in accessing learning media, especially conventional printed learning media. Conventional paper-based learning media often cannot accommodate the specific needs of learners with physical disabilities. Meanwhile, learning media in digital format that are not designed with adequate keyboard navigation accessibility features will also create major barriers for learners with physical disabilities to be able to access them. Consequently, students with physical disabilities are at significant risk of falling behind academically and may struggle to fully realize their potential. To address this issue, the present study focuses on the development of a digital flipbook tailored to the educational needs of students with physical impairments, specifically for the topic of the human digestive system. This investigation adopts a Research and Development (RD) methodology, limited to the development phase. Data were gathered through questionnaires, and a combination of quantitative and qualitative descriptive methods was employed for analysis. The validation of the learning media's appropriateness involved experts in instructional media, content specialists, and field practitioners. The findings from the validation process indicate that the digital flipbook created for teaching the digestive system achieved an 83% feasibility rating, categorized as “highly appropriate.” In summary, the study concludes that the digital flipbook is highly suitable for facilitating the learning of students with physical disabilities on the topic of the human digestive system.